Artbook “Darkness” by O. Mykhed: Specificity of Synthesis of Verbal and Visual Images (Literatures of the World: Poetics, Mentality and Spirituality, 2020)
In the contemporary art space, there is an increasing generalization of meaning, not in textual form, but in visual expression. The change in the cultural paradigm, which took place in the early twentieth century, led to the emergence of visual literature (comics, graphic novels, artbooks), in which the artistic boundaries were mixed, balancing the importance of verbal and visual narratives for understanding content.Interesting in coordinates of intermedial synthesis are artbooks, which combine the features of an art album and a work of art, forming a syncretic genre of experimental prose. Among modern Ukrainian artbooks (project «no message: no text, no image», collections «Flash drive – 2 GB», «Flash drive. Defragmentation», «Underwor (l) d») by Ju. Izdryk, «Alder Blood», «Eden Demes» by M. Babak) the collection «Darkness» by O. Mykhed, is distinguished by original artistic decisions. The visual category is distinguished in the works of such scholars as R. Barth, M. Heidegger, F. Jameson, U. Eco, J.-F. Lyotard, M. Merleau-Ponty. J. Berger, L. Mulvey, W. Mitchell and others have studied the specific features of visual culture and the visual image. The field of visual study has been formed. The subject of visual study is any artistic phenomenon that contains a visual component (such as comics, video games, advertisement etc.) and is related to ideology, social myths, and economics. O. Mykhed’s collection «Darkness» is designed as an artbook. However, the author does not fill the book with photo collages and author's drawings, as we see in the artbooks by Ju. Izdryk and M. Babak, but with paintings by professional artist Sophia Melnyk. Pictures marked with an expressionistic manner of execution and often occupy the entire space of one or two pages. Dark colors, fuzzy lines, blurred images of people, animals, mystical creatures convey the hypertrophied tension of people’s emotions in crisis situations of breaking the established picture of the world.
Keywords: visual literature; visual narrative; artbook; intermediate synthesis; illustration; photo collage